THE EFFECT OF SERVICE QUALITY AND PRODUCT QUALITY ON CUSTOMER SATISFACTION (STUDY AT CFC BATU AJI BATAM) Shandrya Victor Kamanda - Shandrya Victor Kamanda (LPPM Universitas Ibnu Sina, 2023)
The purpose of this study was to determine how much influence of service quality (X1), product quality (X2) on customer satisfaction (Y) at CFC Batuaji Batam. The model in this study is quantitative method, associative with the population in this study are customers who CFC Batuaji Batam. The sampling method using rondom sampling obtained as many as 48 respondents who visited at the time the research was conducted. The research questionnaire instrument uses primary and secondary data. Using SPSS. The analysis method in data processing is validity and reliability test, simple linear regression test, coefficient of determination, hypothesis test (t-test), and Pearson product moment correlation test. The results showed that Service Quality (X1), Product Quality (X2), also had a significant effect on Customer Satisfaction (Y). Therefore, it is important to maintain these variables on quality standards because they have a significant impact on customer satisfaction.